О гнездовании большого баклана на Соленоозерском участке Ченоморского биосферного заповедника - Москаленко, Ю.А. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
The Cormorant appeared on breeding in the oak-tree clumps at the Salt-Lake area of the Black Sea Biosphere Reserve in 2008. Its nesting here is a real threat for unique local associations. The necessity of further perfection of complex measures on a management of the Cormorant population in the Black Sea Biosphere Reserve is discussed in the present report.